Enhancing anaerobic endurance in football players: A comparative study of 3-a-side and 5-a-side small-sided games - Kusuma, Ketut Chandra Adinata; Artanayasa, I Wayan; Sudiana, I Ketut; Yudi, Alex Aldha (Journal Sport Area, 2023)
The demands of modern football are to play at a high tempo for two 45-minute games or more. Aerobic endurance, power, maximum speed, and acceleration are not enough for today players. The purpose of this study was to reveal the impact of 3-a-side and 5-a-side small-sided games (SSGs) on increasing anaerobic endurance. This study employed a quasi-experimental design with a pretest-posttest group design involving 40 young football players who were randomly assigned to practice 3-a-side and 5-a-side for 4 weeks. Before and after carrying out the 4-week training, a Repeat Sprint Ability Test (RSAT) was performed to measure anaerobic endurance. The paired sample t-test was used to determine whether there was an effect of the exercise, and the independent sample t-test was used to see whether there was a difference in the results between the two groups at the 1% significance level. Before carrying out the parametric test, the data were first tested for normality using Kolmogorov-Smirnova and for homogeneity using Levene's. It was revealed that 3-a-side and 5-a-side SSGs were both capable of increasing anaerobic endurance, but there was no significant difference between the two groups. It can be concluded that anaerobic endurance can be increased within four weeks by using these two methods. The recommendations from this study are to conduct a randomized controlled trial with a larger and more diverse sample to validate and extend these findings. Further studies also need to explore the effects of SSGs exercise on anaerobic endurance over a longer exercise period and in different age groups to gain a more comprehensive understanding.